Quaternary glaciation of the Bale Mountains, Ethiopia. - Osmastom, H. A.; Mitchell, W. A.; Osmaston, J. A. N. (Journal of Quaternary Science, 2005)
Central Ethiopia comprises a high plateau at 2000-3000 m, formed from Tertiary lava flows and bisected by the Eastern African Rift. Ten volcanic mountains rise to altitudes of just over 4000 m, but on only three has Quaternary glaciation been substantiated by published field observations. On the Bale Mountains (4400 m), a previous report based on limited evidence proposed an ice-cap extending to 600 km2. Based on aerial photographs and ground surveys, this paper reports evidence of a more complex situation. A wide spread of large erratic boulders on the plateau records a central ice cap of 30 km2, though ice probably extended for a further 40 km2. Further north two groups of deeply incised and clearly glaciated valleys contain moraines and roches moutonnées (60 km2). On interfluves between them and on the open north slopes are moraines from an earlier stage of the same glaciation or from a distinct older event. Altogether about 180 km2 may have been glaciated. Cores dated by 14C from inside and outside the glaciated area suggest that at least the northern valley glaciers may date from the Last Glacial Maximum. Estimated equilibrium line altitudes for these glaciers and the ice-cap are 3750-4230 m.